Teachers’ self-perception of scientific competences: a gender approach - Garcés-Gómez, Yeison Alberto; Alzate, Valentina Cadavid; Rodríguez Ortiz, Angélica María; Lara Escobar, Rubén Darío (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study analyses the self-perception of 274 teachers from public, urban, and rural schools in Manizales, Colombia, using a Likert scale instrument developed considering the scientific competencies determined by UNESCO. In the analysis of the results, it was found that, even though in the sample analyzed, women have greater training in research and scientific competencies, their perception of their abilities in this aspect is lower than that of men. With the Mann-Whitney U test and rank-biserial correlation, it was possible to test the alternative hypothesis that the female self-perception of capabilities is lower than the male for each question. The instrument was validated with the internal consistency index with an α=0.98. Additionally, the instrument has been validated with a confirmatory factor analysis, obtaining values of comparative fit index (CFI) of 0.869 and Tucker-Lewis’s index (TLI) of 0.858 with RMSEA and SRMR of 0.103 and 0.063, respectively. The paper provides insights into the self-perception of scientific competencies among teachers, which can inform teacher training and professional development programs. The study highlighted the gender gap in self-perception of scientific competencies, which can inform policies and interventions to promote gender equity in science education.